Penguatan Etika dan Tanggung Jawab Sosial Mahasiswa Melalui Implementasi Budaya Organisasi yang Berkelanjutan di HIMA PPKn Universitas Pamulang - Utaminingsih, Sri; Shella Rachmawaty; Haryanti, Amelia; Hendri (Jurnal Loyalitas Sosial: Journal of Community Service in Humanities and Social Sciences, 2024)
Ethics and social responsibility are important aspects in shaping individuals who are responsible and care about society. Students are future agents of change who need to be formed within the framework of ethics and social responsibility. The Pancasila and Citizenship Education Study Program Student Association (HIMA PPKn) understands the importance of this aspect and has started efforts to implement it in a sustainable organisational culture. The purpose of this activity is to strengthen students' ethics and social responsibility through the implementation of a sustainable organisational culture in HIMA PPKn.  The method of implementing this activity involves developing an organisational culture that promotes ethics, integrity, participation in social activities, and self-development. In addition, students also receive counselling related to ethics and social responsibility. Sustainable social programmes are run as a form of positive contribution to society and the environment. The result of this activity is an increased understanding of ethics and social responsibility among students, especially the management of HIMA PPKn. They grow and develop as socially responsible individuals who are able to provide concrete benefits to society. The social programmes run also have a positive impact on the community. Suggestions for the future evaluation and expansion of programs that have been carried out are important steps in strengthening a sustainable organizational culture in developing student ethics and social responsibility. Furthermore, it is hoped that this activity can be an inspiration for other student organisations to strengthen these values in their organisational culture and make a greater contribution to society and the nation.